MODERN METHODS OF TREATMENT OF BACTERIAL VAGINOSIS IN WOMEN - Aljanova, M.D.; Muslimova S.А.; Бабаєва, Г.І.; Mamedli, G.H.; Aghakishiyeva, L.G.; Javanshir P.А. (World of Medicine and Biology, 2025)
With the purpose to compare the effectiveness of different treatment regimens for bacterial vaginosis 67 patients with bacterial vaginosis detected by vaginal microscopy (age 18–45 years) were observed: 32 patients who received therapy by preparation based on neomycin sulfate, ornidazole, prednisolone sodium phosphate and econazole nitrate; 35 patients who received therapy with intravaginal metronidazole in gel form. The highest clinical efficacy (93.7 % according to R. Amsel criteria) was observed in patients of the group who received combination therapy (neomycin sulfate, ornidazole, prednisolone sodium phosphate and econazole nitrate; p